2020
DOI: 10.3311/ppci.14190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Basalt Fiber on the Performance of Stone Mastic Asphalt

Abstract: Stone Mastic Asphalt (SMA) is a mixture design against rutting caused by intensive and heavy traffic loads. While modified bitumen needs to be used in this mixture, the use of cellulosic fibers is essential to prevent the infiltration of bitumen during the carriage of mixture due to high bitumen content. In this study, the effects of basalt fiber on the performance of SMA mixtures is investigated as an alternative to cellulosic fiber admixtures in the prevention of draindown. Raw materials commonly used in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…La estabilización de mezclas asfálticas, especialmente mediante el uso de inhibidores de drenaje como las fibras de basalto, desempeña un papel crucial en la ingeniería de pavimentos y carreteras (Cetin et al, 2021). La importancia de esta práctica radica en su capacidad para mejorar significativamente la durabilidad, resistencia y vida útil de las superficies pavimentadas.…”
Section: Importancia De La Estabilización De Mezclas Asfálticas Stone...unclassified
“…La estabilización de mezclas asfálticas, especialmente mediante el uso de inhibidores de drenaje como las fibras de basalto, desempeña un papel crucial en la ingeniería de pavimentos y carreteras (Cetin et al, 2021). La importancia de esta práctica radica en su capacidad para mejorar significativamente la durabilidad, resistencia y vida útil de las superficies pavimentadas.…”
Section: Importancia De La Estabilización De Mezclas Asfálticas Stone...unclassified
“…The inclusion of BFs in asphalt mixes can improve their water resistance. Cetin et al [ 45 ] found that the indirect tensile strength value at 0.6% of BFs was 75.6% higher than that of the control group. According to the quantitative results of the logistic damage model, for 0.4% dosing under 6 mm BF makes AC-13 mix, compared with the control group, the degree of freeze-thaw damage of asphalt mix is significantly reduced by about 25%, and the damage growth rate is significantly decreased by about 45% [ 62 ].…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…La prueba de susceptibilidad a la humedad de las mezclas, definida como la alteración de la mezcla asfáltica por el agua, es decir que, si el agua penetra en la mezcla asfáltica, daña la unión entre los agregados y el cemento asfáltico, acelerando así el deterioro del pavimento (Çetin, Evirgen, Karslioglu, y Tuncan, 2020). En esta prueba, Park y colaboradores mencionaron que la resistencia a la humedad de la mezcla asfáltica se determina comparando la resistencia a la tracción indirecta en estado seco y después del estado de congelación-descongelación de agua (Park, Shoukat, Yoo, y Lee, 2020).…”
Section: Métodos Utilizados Para Evaluar Las Mezclas Asfálticas Con F...unclassified